Interweaving Neuroscience, Quantum Science and Andean Wisdom: Health Sciences In-formation from the Educational Paradigm of Allin Kawsay (Good Living) - Sarmiento Peralta, Giusseppe Geraldes; Arevalo Arevalo, Carlos; Callan Bacilio, Richard (Iatreia, 2025)
Introduction: Health sciences education has not been exempt from the challenges of the post-pandemic context. In light of these difficulties, it has become urgent to find new strategies to address them. Therefore, it is worth considering certain approaches rooted in Andean native wisdom that may prove useful. Objectives: To describe and explore the educational paradigm of allin kawsay or “good living” (PEAK) through two fundamental questions: How do we conceive of the subject of education? And how can we educate them to reach their full potential? Methods: The term ‘in-formation’ was reconceptualized, and the educational paradigm of buen vivir was operationalized into four dimensions: allin yuyay (“good thinking”), allin sonqoy (“good feeling”), allin rimay (“good speaking”), and allin ruway (“good doing”). Results: The PEAK represents a pedagogical alternative with great potential for health sciences education, as it fosters a transdisciplinary dialogue between Andean wisdom and cutting-edge discoveries in frontier sciences such as neuroscience and quantum science. Conclusions: This new educational paradigm offers innovative approaches to highly complex issues and can also holistically address the two research questions, thereby fostering comprehensive training in health and life sciences.